2023
DOI: 10.3389/fpubh.2023.1081706
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of smoking and depression among US adults: NHANES (2005–2018)

Abstract: BackgroundThe relationship between smoking and depression remains controversial. This study aimed to investigate the association between smoking and depression from three aspects: smoking status, smoking volume, and smoking cessation.MethodsData from adults aged ≥20 who participated in the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2018 were collected. The study gathered information about the participants' smoking status (never smokers, previous smokers, occasional smokers, dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
(38 reference statements)
1
17
0
1
Order By: Relevance
“…In a Mendelian randomization study for 462,690 participants from the UK Biobank, smoking was a significant risk factor for depression (OR: 1.99 [1.71–2.32) across both lifetime smoking and smoking initiation [ 24 ]. A recent cross-sectional study demonstrated that depression was more significantly associated with previous smokers (OR: 1.25 [1.05–1.48]) and occasional smokers (OR: 1.84 [1.39–2.45]), compared with never smokers [ 9 ]. In addition, longitudinal analyses showed that daily smoking increased the risk for subsequent development of depression among adolescents [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Mendelian randomization study for 462,690 participants from the UK Biobank, smoking was a significant risk factor for depression (OR: 1.99 [1.71–2.32) across both lifetime smoking and smoking initiation [ 24 ]. A recent cross-sectional study demonstrated that depression was more significantly associated with previous smokers (OR: 1.25 [1.05–1.48]) and occasional smokers (OR: 1.84 [1.39–2.45]), compared with never smokers [ 9 ]. In addition, longitudinal analyses showed that daily smoking increased the risk for subsequent development of depression among adolescents [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review for 148 studies indicated that exposure to smoking at baseline led to the increased incidence of later depression [ 8 ]. Wu et al demonstrated that smoking amount was positively associated with the risk of depression in a cross-sectional study [ 9 ]. In a systematic review, long-term smoking cessation over 10 years was negatively associated with the risk of depression [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Covariables were chosen based on previous research (Wu et al, 2023; You et al, 2023). Demographic characteristics were extracted from the demographic questionnaire, including age, gender, race/ethnicity, marital status, family poverty income ratio, and education level.…”
Section: Methodsmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES), a nationally representative survey conducted in the United States, collects comprehensive data on various health-related factors, including smoking habits and sleep parameters (Wu et al, 2023). By leveraging NHANES data from 2007-2020 March, we can explore the potential link between smoking and poor sleep quality while accounting for potential confounders such as age, gender, race/ethnicity, education level, marital status, and body mass index (BMI) (You et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…According to a meta‐analysis by Zenebe et al, 25 a high global prevalence of depressive symptoms was found among the older population ranging from 7.7% to 81.1%. Multiple factors are associated with geriatric depressive symptoms, such as being female, 26 older age, 27 being single or divorced, 28 lower educational attainment, unemployment, low income, 29 low self‐esteem, 30 loneliness or living alone, 31 social deprivation, 32 presence of chronic illness or poor health status, 33 lack of health insurance, 34 smoking habit, 35 cognitive impairment and a history of depressive symptom 25 . Despite geriatric depressive symptoms being a major problem, they are often undiagnosed, underdiagnosed, undertreated or diagnosed late 36 .…”
Section: Introductionmentioning
confidence: 99%